2012
DOI: 10.1507/endocrj.ej11-0157
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion and insulin sensitivity on the oral glucose tolerance test (OGTT) in middle-aged Japanese

Abstract: InsulIn resistance and impaired insulin secretion are considered the primary pathophysiological factors in the development of type 2 diabetes [1]. Although hyperglycemic and euglycemic clamp studies are wellestablished methods of assessing insulin secretion and insulin sensitivity [2,3], the oral glucose tolerance test (OGTT) is a simpler and less expensive method that provides estimates of both factors. As a measure of insulin secretion, insulinogenic index is highly correlated with the acute insulin response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 32 publications
2
33
1
Order By: Relevance
“…Data from consecutive 2,264 individuals who received the checkup including a 75 g OGTT with immunoreactive insulin (IRI) measurement between April 2006 and March 2010 [18] without a history of DM or gastrectomy and not taking glucocorticoid or anticancer drugs were used. Among them, the number of subjects with the ADA-defined NGT [19] was 1,209.…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Data from consecutive 2,264 individuals who received the checkup including a 75 g OGTT with immunoreactive insulin (IRI) measurement between April 2006 and March 2010 [18] without a history of DM or gastrectomy and not taking glucocorticoid or anticancer drugs were used. Among them, the number of subjects with the ADA-defined NGT [19] was 1,209.…”
Section: Study Samplementioning
confidence: 99%
“…After an overnight fast, a standard 75 g OGTT was performed as previously described [18]. Plasma glucose (PG) was analyzed by the glucose oxidase method (Automatic Glucose Analyzer ADAMS Glucose GA-1160, Arkray, Kyoto) and immunoreactive insulin (IRI) by the chemiluminescence method (ADVIA Centaur, Siemens Medical Solutions).…”
Section: Measurement Of Plasma Glucose and Insulin And Diagnosis Of mentioning
confidence: 99%
“…Similarly, in a study of overweight/obese adolescents, subjects with HbA1c 5.7 to <6.5% had significantly lower insulin sensitivity and β-cell function versus those with normal HbA1c [25]. Previous studies had demonstrated that impairment of insulin secretion and insulin sensitivity starts from the NGT range of 2-h plasma glucose, and minimally elevated glucose may indicate the onset of insulin sensitivity and β-cell function impairment [26]. Our study demonstrated that after adjustment for various confounding factors including FPG and 2h-β-cell function and isolated high HbA1c PG, the OR of insulin resistance (IR-Matsuda ISI) and impaired early β-cell response to insulin sensitivity (IB-DI30) remained significant.…”
Section: Discussionmentioning
confidence: 87%
“…Subjects with IGT have impaired late-phase insulin secretion and increased insulin resistance (IR) in skeletal muscle. In contrasts, subjects with IFG have impaired early -phase insulin secretion and increased IR in liver [6][7][8]. Similarly there are some discrepancies between the clinical features of IFG and IGT.…”
Section: Plasma Glucose Levels and Prediction Of Future Type 2 Diabetesmentioning
confidence: 99%
“…Similarly there are some discrepancies between the clinical features of IFG and IGT. Subjects with isolated IFG are more insulin resistant, and subjects with isolated IGT exhibits a more severe deficit in insulin secretion [8]. IFG and IGT have been associated with other features of insulin resistance, including dyslipidaemia, hypertension, abdominal obesity, microalbuminuria, endothelial dysfunction, and markers of inflammation and hypercoagulability [5].…”
Section: Plasma Glucose Levels and Prediction Of Future Type 2 Diabetesmentioning
confidence: 99%